Acoustical imaging : techniques and applications for engineers - Gan, Woon Siong (Wiley, A John Wiley & Sons, Ltd., Publication, 2012)
"Acoustical Imaging starts with an introduction to the basic theories and principles of acoustics and acoustical imaging, then progresses to discuss its varied applications: nondestructive testing, medical imaging, underwater imaging and SONAR and geophysical exploration. The author draws together the different technologies, highlighting the similarities between topic areas and their common underlying theory. Some advanced topics are also described such as nonlinear acoustical imaging and its application in nondestructive testing, application of chaos theory to acoustical imaging, statistical treatment of acoustical imaging and negative refraction"--Provided by publisher